Investigation on Flexural Behaviour of Cold Formed Steel Latticed Built-Up I Section with Drop Web - N. Nandhini; K. Sudha (Asian Journal of Engineering and Applied Technology, 2018)
This paper deals with the study of flexural behaviour of cold formed latticed built-up I beam with drop web for various sections by varying depth, thickness and span length of the section. The numerical analysis was carried out by FEM software ABAQUS 6.13[11]. The experimental works carried out by Cheng Yu and Benjamin W. Schafer (2006) [1] were taken for validating the numerical analysis procedure. It provides a cost effective way to explore the performance of products in a virtual environment. The ultimate capacity is obtained by performing both linear and non-linear analysis. Theoretical investigation as per AISI specification was carried out for all the specimens to check the accuracy of the design proposal. Numerical finite element procedure is used to instruct the effect of various parameters on behavior of beams. The critical load and different modes of failure are studied by this numerical investigation. Comparison between deformed shape and load vs. displacement curves of I section with drop web were presented.